Organizational Risk Taking: Adaptation versus Variable Risk Preferences - Denrell, J (2008)
The observed association between performance and organizational risk taking has usually been attributed to the influence of performance on risk preferences. Here I show how a simple model of adaptation, which only assumes that organizations avoid activities with poor past performance, can explain the empirically observed U-shaped association between risk and return. The model also makes novel predictions, which are shown to be consistent with the data. The findings suggest that risk taking may be a by-product of adaptation rather than a deliberate choice motivated by variable risk preferences.